A Study on The Domestication of Tiger Snail (Babylonia spirata l) in An Abanont Brackish Water Pond at Different Stocking Denstities - Sri Rejeki; Titik Susilowati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
Tiger snail (Babylonia spirata L) is one of molllucs family which has a good economic value both for local and international market. This study was aimed to find out the effects of different stocking densities on the specific growth rate and survival rate of tiger snail cultured in an abandon brackish water pond. A completely randomized design was applied in this research. The treatments were A (18 tiger snail/0,15m2), B (22 tiger snail/0,15m2), C (26 tiger snail/0,15m2), D (30 tiger snail/0,15m2), E (34 tiger snail/0,15m2). Each treatment was repicated three times. Plastic baskets at the size of 0.15 were used as a cage for holding system. Tiger snail at initial average body weight of 8 gram approximately was used as tested animal. The study was carried out at an abandon brackish water pond Desa Tapak Kecamatan Semarang Barat, Central java Province from May – July 2007. The results show that different stocking densities affected the specific growth rate and food conversion ratio of tiger snail significantly. Stocking density of 18 snail/0.15 m2 gave the highest specific growth rate (2.07%/day) and food conversion ratio of 1,747. Keyword: Domestication, tiger snail, stocking density, abandon brackish water pond